High consumptions of grain, fish, dairy products and combinations of these are associated with a low prevalence of metabolic syndrome. Issue 9 (14th August 2007) - Ruidavets, Jean-Bernard; Bongard, Vanina; Dallongeville, Jean; Arveiler, Dominique; Ducimetière, Pierre; Perret, Bertrand; Simon, Chantal; Amouyel, Philippe; Ferrières, Jean
Abstract : Objective: To analyse the relation between various food groups and the frequency of insulin resistance syndrome (IRS). Design: A sample of 912 men aged 45–64 years was randomly selected. Questionnaires on risk factors and a three consecutive day food diary were completed. Height, weight, waist circumference, and blood pressure were measured. A fasting blood sample was analysed for lipid and glucose measurements. The NCEP-ATP-III definition was used to assess IRS. Data were analysed according to quintiles of food groups and medians of dairy products, fish, or cereal grains. Results: The prevalence of IRS was 23.5%. It reached 29.0%, 28.1% and 28.1% when the intake was below the median for fish, dairy products, and grain, respectively. When consumptions of all three types of food were higher than the median, the prevalence reached 13.1%, and when they were lower, the prevalence was 37.9% (p<0.001). In logistic regression adjusted for confounders (centre, age, physical activities, education level, smoking, dieting, alcohol intake, treatments for hypertension and dyslipidaemia, energy intake, and diet quality index) the odds ratios for IRS (above median value v below) were 0.51 (95% confidence interval, 0.36 to 0.71) for fish, 0.67 (0.47 to 0.94) for dairy products, and 0.69 (0.47 to 1.01) for grain. When intakes of all three kinds of food were high, the OR was 0.22 (0.10 to 0.44). Conclusions: A high consumption of dairy products, fish, or cereal grains is associated with a lower probability of IRS. The probability decreases when intakes of all three types of food were high.